Rabies is still a fatal but neglected disease: a case report - Y. A. Amoako (BMC, 2021)
Abstract Background Rabies, caused by a lyssavirus, is a viral zoonosis that affects people in many parts of the world, especially those in low income countries. Contact with domestic animals, especially dogs, is the main source of human infections. Humans may present with the disease only after a long period of exposure. Nearly half of rabies cases occur in children <15 years old. We report on a fatal case of rabies in a Ghanaian school child 5 years after the exposure incident, and the vital role of molecular tools in the confirmation of the diagnosis. Case presentation The patient, an 11-year-old junior high school Ghanaian student from the Obuasi Municipality in Ghana, presented with aggressive behavior, which rapidly progressed to confusion and loss of consciousness within a day of onset. Her parents reported that the patient had experienced a bite from a stray dog on her right leg 5 years prior to presentation, for which no antirabies prophylaxis was given. The patient died within minutes of arrival in hospital (within 24 hours of symptom onset). Real-time polymerase chain reaction testing of cerebrospinal fluid obtained after her death confirmed the diagnosis of rabies. Subsequent phylogenetic analysis showed the virus to belong to the Africa 2 lineage of rabies viruses, which is one of the predominant circulating lineages in Ghana. Conclusion The incubation period of rabies is highly variable so patients may only present with symptoms long after the exposure incident. Appropriate molecular testing tools, when available as part of rabies control programmes, are vital in confirming cases of rabies.